BAIAP2L1 accelerates breast cancer progression and chemoresistance by activating AKT signaling through binding with ribosomal protein L3 - Deng, Ning; Zhang, Xiupeng; Zhang, Yong (Cancer science, 2023)
BAI1‐associated protein 2‐like 1 (BAIAP2L1), also known as insulin receptor tyrosine kinase substrate, modulates the insulin network; however, its function in breast cancer has not been explored. Immunohistochemical analysis of 140 breast cancer specimens (77 triple‐negative and 63 nontriple‐negative cases) indicated that BAIAP2L1 expression was higher in breast cancer tissues (56/140, 40%) than in normal breast tissues (28.3%, 15/53; p < 0.001). BAIAP2L1 expression in breast cancer was correlated with triple‐negative breast cancer (p = 0.0013), advanced TNM stage (p = 0.001), lymph node metastasis (p = 0.001), and poor patient prognosis (p = 0.001). BAIAP2L1 overexpression could accelerate breast cancer proliferation, invasion, and stemness in vivo and in vitro, possibly through the activation of AKT, Snail, and cyclin D1. Treatment with the AKT inhibitor LY294002 reduced the effects of BAIAP2L1 overexpression on breast cancer cells. BAIAP2L1 may bind to the AA202‐288 of ribosomal protein L3 (RPL3) within its SRC homology 3 (SH3) domain, the loss of which may abolish the transduction of the AKT signaling pathway by promoting the degradation of PIK3CA. Moreover, BAIAP2L1 overexpression may induce chemotherapy resistance, with BAIAP2L1 expression being higher in patients with advanced Miller grades than those with lower grades. Our results indicated that BAIAP2L1 promotes breast cancer progression through the AKT signaling pathway by interacting with RPL3 through its SH3 domain. Our results indicated that BAIAP2L1 promotes breast cancer progression and chemotherapy resistance via the AKT signaling pathway by stabilizing PIK3CA via interacting with RPL3 through its SH3 domain.